‘Can you flip it?’ A case study of teaching physical sciences in rural schools through the rural blended learning strategy - Nkanyani, Tebogo E.; Mudau, Awelani V.; Sikhosana, Lettah (Frontiers in Education, 2025)
AimThis study reports on the Physical Sciences teacher’s teaching difficulties when teaching with the Rural Blended Learning Strategy (RBLS), which is based on the flipped classroom approach, and the implications of that on his self-directedness, social presence, and teaching presence.MethodsIt was a qualitative case study which relied on semi-structured interviews, focus group interviews, and classroom observations of the Physical Sciences learning process. The sampled population consisted of one Physical Sciences teacher and his learners, who were purposefully sampled as their school is a rural school. The data were photographed, audio, and video recorded to provide pictures and a transcript. The RBLS’s Detailed Analysis System was also crucial in the data analysis process.ResultsIn addition to inadequate institutional support and the Physical Sciences teacher’s insufficient technology skills, the teacher was not self-directed since he did not improvise through his smartphone to flip the classroom by blending the learning process at school or from the comfort of his home, when the laptop he shares with his colleagues was unavailable. This eliminated the possibility of shaping self-directed learners in his class. Additionally, by taking time to set up the learning management system and not using video-conferencing platforms, the teacher demonstrated an inadequate teaching presence, inhibiting the social presence in the process.ConclusionFailure and reluctance from the teacher to implement the RBLS demonstrate insufficient self-directedness, teaching, and social presence. We recommend a sustained, long-term professional development on the RBLS to ensure its effective integration in the Physical Science teaching practice, while the School Governing Bodies (SGBs) fine-tune their institutional support.